The Changing Wealth of Nations 2021 : Managing Assets for the Future - World Bank (Washington, DC: World Bank, 2021)
It is now clear that a narrow focus on the growth of gross domestic product (GDP) is insufficient to achieve humanity’s aspirations for sustainable prosperity. Wellfunctioning ecosystems and educated populations are requisites for sustainable wellbeing. These and other too-often-neglected ingredients of national wealth must be addressed if the development path is to be sustainable. The Changing Wealth of Nations 2021: Managing Assets for the Future provides the most comprehensive accounting of the wealth of nations, an in-depth analysis of the evolution of wealth, and pathways to build wealth for the future. This report—and the accompanying global database—firmly establishes comprehensive wealth as a measure of sustainability and a key component of country analytics. It expands the coverage of wealth accounts and improves our understanding of the quality of all assets, notably, natural capital. Wealth—the stock of produced, natural, and human capital—is measured as the sum of assets that yield a stream of benefits over time. Changes in the wealth of nations matter because they reflect the change in countries’ assets that underpin future income. Countries regularly track GDP as an indicator of their economic progress, but not wealth, and national wealth has a more direct and long-term impact on people’s lives. This report provides a new set of tools and analysis to help policy makers navigate risks and to guide collective action. Wealth accounts can be applied in macroeconomic analysis to areas of major policy concern such as climate change and natural resource management. This report can be used to look beyond GDP, to gauge nations’ economic well-being, and to promote sustainable prosperity.